Tramadol Versus Diclofenac in Pain Management after Cesarean Section: A Cost Analysis Study - Sara Merrikhihaghi; Amir Farshchi; Boheireh Farshchi; Samireh Farshchi; Farid Abedin-Dorkoosh (Tehran University of Medical Sciences, 2015)
Introduction: Postoperative pain is considered frequently as one of the major problems in subjects after cesarean delivery. Meanwhile, the main analgesic drugs are opioids and non-steroidal anti-inflammatory drugs, side-effects such as nausea, vomiting, and sedation have been reported by opioids. Economic evaluation of analgesics is an important criterion in clinical practice and efficiency of the health system services. The aim of this study was to compare the efficacy and cost analysis of diclofenac versus tramadol for post-cesarean pain in postpartum women. Patients and Methods: This study has been undertaken based on a randomized clinical trial that has evaluated postoperative pain in a double-blinded, randomized, single-dose comparison of tramadol intramuscular injection, 100 mg (group T) and diclofenac suppository, 100 mg (group D) given alone-single dose in 200 patients who had elective cesarean delivery. All patients were assessed at 0, 6, 12, and 24 h post-operation for pain degree (by Visual Analog Score: 1-10), nausea and vomiting incidence. Our outcomes assessment was based on the reduction in pain degree. For cost estimating of therapeutic schemes, we computed the direct costs of the analgesics (unitary cost) and disposable materials such as needles, syringes, and alcoholic pads (Padcols®). Average cost-effectiveness ratio (ACER) calculated for comparison. Results and Discussion: The efficacy of tramadol and diclofenac were not different significantly (P = 0.06). Nausea and vomiting were minimal with all treatments. Total costs in T group were 43.35 USA Dollar (USD) and in D group were 12.1 USD. ACER for tramadol was 9.14 USD and 2.85 USD for diclofenac per one degree reduction in pain. Thus, ACER indicated that the cost of tramadol in this study was 3.21 times more than diclofenac resulted with the same effectiveness. Conclusions: It has been concluded that diclofenac is a more cost-effective choice of treatment in comparison with tramadol for post-cesarean pain management.